2022
DOI: 10.3389/fphar.2022.853289
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Traditional Chinese Medicine in Treatment of Myocardial fibrosis

Abstract: Effective drugs for the treatment of myocardial fibrosis (MF) are lacking. Traditional Chinese medicine (TCM) has garnered increasing attention in recent years for the prevention and treatment of myocardial fibrosis. This Article describes the pathogenesis of myocardial fibrosis from the modern medicine, along with the research progress. Reports suggest that Chinese medicine may play a role in ameliorating myocardial fibrosis through different regulatory mechanisms such as reduction of inflammatory reaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…In addition, galangin could reduce bleomycin‐induced inflammatory cell activation such as CD4 + CD69+, CD8 + CD69 + T cells and dendritic cells, thereby reducing inflammatory cells in lung tissue of mice (Wang et al, 2020). Furthermore, myocardial fibrosis is one of the main manifestations of myocardial remodeling, which can lead to heart failure and death (Ren et al, 2022). Thangaiyan et al reported that pretreatment with galangin decreased heart rate, lipid peroxidation and upregulated the blood pressure in ISO‐induced rats.…”
Section: Pharmacological Activities Of Galanginmentioning
confidence: 99%
“…In addition, galangin could reduce bleomycin‐induced inflammatory cell activation such as CD4 + CD69+, CD8 + CD69 + T cells and dendritic cells, thereby reducing inflammatory cells in lung tissue of mice (Wang et al, 2020). Furthermore, myocardial fibrosis is one of the main manifestations of myocardial remodeling, which can lead to heart failure and death (Ren et al, 2022). Thangaiyan et al reported that pretreatment with galangin decreased heart rate, lipid peroxidation and upregulated the blood pressure in ISO‐induced rats.…”
Section: Pharmacological Activities Of Galanginmentioning
confidence: 99%
“…First, danshinone has been suggested to reverse the increase in the levels of collagen type 1 (Col1), collagen type 3 (Col3) and α-smooth muscle actin (α-SMA) in HF rats induced by ligation of the left anterior descending branch (LAD) of the coronary artery through upregulating miR-205-3p, miR-29b, or miR-618 ( Yang et al, 2023 ). Second, MF is achieved by downregulating the TGF-β/SMAD2/3 signaling pathway ( Ren et al, 2022 ).…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
“…Other TCMs, such as curcumin, earthworms and ginsenoside, have therapeutic effects on MF ( Yu et al, 2019 ; Lai et al, 2015 ; Wang et al, 2021 ). Curcumin decreases cardiac fibrogenesis by activating SIRT1, increasing Nrf2, and increasing NADPH oxidase subunits ( Sadoughi et al, 2021 ; Ren et al, 2022 ). Earthworms can inhibit MF by inhibiting the levels of MF-related proteins in H9c2 cells ( Huang et al, 2019 ).…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
See 2 more Smart Citations